2010
DOI: 10.1111/j.1464-410x.2009.09156.x
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine‐1‐phosphate pathway is upregulated in response to partial urethral obstruction in male rats and activates RhoA/Rho‐kinase signalling

Abstract: contractility studies, and for mRNA and protein analyses of major S1P/ROK pathway constituents via real-time polymerase chain reaction and Western blotting, respectively. In addition, early-passage SM cells were transfected with recombinant sphingosine kinase (SPHK, the enzyme that converts sphingosine to S1P). RESULTSBladders from PUO rats had greater mRNA expression of the S1P2 and S1P3 receptors, as well as SPHK1, than the sham controls (4.78, 2.04 and 2.72 times, respectively). PUO rats also had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
(62 reference statements)
0
21
1
Order By: Relevance
“…RPL19 was determined to be more stable than either ␤-actin or GAPDH in a rat model of partial bladder outlet obstruction. However, we did not find any effect of aging, diabetes, or castration on these three housekeeping genes (8).…”
Section: Animals and Tissuescontrasting
confidence: 88%
“…RPL19 was determined to be more stable than either ␤-actin or GAPDH in a rat model of partial bladder outlet obstruction. However, we did not find any effect of aging, diabetes, or castration on these three housekeeping genes (8).…”
Section: Animals and Tissuescontrasting
confidence: 88%
“…15 In brief, total RNA was extracted from 100 Kg of lung tissues using an RNeasy total RNA extraction kit (Qiagen, Chatsworth, CA). Then, 2 Kg of total RNA was used in a complementary DNA (cDNA) reaction.…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…One or more of these receptors have been reported to mediate the contractile effect of S1P in a variety of smooth muscle preparations. It has been reported that S1P-induced contractions were mediated via S1PR2 receptors in the urinary bladder [28, 31, 37], myometrium [25], airway smooth muscle [26], esophageal [27] and gastric smooth muscle [29, 46]. S1P-induced contraction of gastric smooth muscle is also mediated in part by S1PR1 receptors [29, 46].…”
Section: Discussionmentioning
confidence: 99%
“…According to Chiba et al (2010), S1P-induced contraction of murine bronchial smooth muscle was abolished by Y-27632, an inhibitor of Rho kinase indicating a role for Rho-kinase pathway of calcium sensitization in S1P-induced contraction of the bronchial smooth muscle. The Rho kinase pathway of calcium sensitization has also been implicated in S1P-induced contraction of guinea-pig trachea [38], urinary bladder [31, 37], human airway smooth muscle [26] and porcine retinal arterioles [51]. Kim et al have reported a role for the PKC pathway of calcium sensitization in S1P-induced contraction of feline esophageal smooth muscle cells [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation